Compact wideband wide-angle van atta retroreflector with suppressed structural mode - Yan, Libin (2022)
A passive miniaturized wideband, wide-angle, and low structural mode Van Atta retroreflector for copolarized applications is presented. The proposed Van Atta retroreflector is composed of eight radiating elements interconnected in pairs with a planar feeding network of microstrip lines. Furthermore, the radiating element consists of a compact dielectric-filled open-ended waveguide. The dielectric filling is designed with rectangular pyramid trench to ensure the broadband feature of the open-ended waveguide, while minimizing the dimensions. In addition, the microstrip lines are designed on the two side walls of the Van Atta retroreflector, which are parallel to the incident plane, to suppress the structural mode contributed by the feeding network. The designed Van Atta retroreflector is verified by simulations and experiments with 40% fractional bandwidth centered at 10 GHz. The monostatic radar cross section (RCS) shows that the -10 dB beamwidth is about 80^circ over the frequency range of interest. Meanwhile, the bistatic RCS indicates that the sidelobe level is less than -10 dB for copolarized retroreflection from -25^circ to 25^circ over the frequency range of 9.5-10.5 GHz.